Case Report: Atypical Presentation of Neuroretinitis in a Middle-aged Woman with Pre-existing Maculopathy. Issue 9 (September 2021) - Yadav, Sandhya; Kumawat, Devesh; Afroz, Khan Shama; Patel, Siddharth; Samanta, Ramanuj
Abstract : SIGNIFICANCE: Neuroretinitis classically presents with sudden vision loss, disc edema, and macular star formation. However, the classical triad may not always be seen, especially in the case of a pre-existing macular disorder. A thorough clinical examination may still clinch the appropriate diagnosis and prevent unwarranted treatment. PURPOSE: This study aimed to report a case of neuroretinitis in an adult woman with pre-existing type 2 macular telangiectasia where the classical pattern of exudation could not be seen. CASE REPORT: A 48-year-old woman, type 2 diabetic and hypertensive, presented with sudden painless blurring of vision in the right eye for the past 1 week. Macula in both eyes had loss of transparency and intraretinal crystalline deposits and pigments. The right eye had hyperemic edematous disc with peripapillary retinal hemorrhages and hard exudates. Color vision was grossly abnormal, and a centrocecal scotoma was noted on visual field analysis in the right eye. After a normal systemic evaluation, a diagnosis of right eye neuroretinitis and coexistent bilateral type 2 macular telangiectasia (nonproliferative type) was made. Unilateral painless visual loss, severe dyschromatopsia, and peripapillary hard exudates pointed to the correct diagnosis of neuroretinitis. Observation was advised, and visual acuity improved spontaneously. The disc edema resolved with consequent optic atrophy. CONCLUSIONS: Absence of the classical "macular star" appearance does not refute the diagnosis of neuroretinitis when pre-existing maculopathy is present.